Grensverleggende beelden Literaire transfer uit de Lage Landen naar Zuid-Europa - Gentile, Paola; Ross, Dolores (Lage Landen Studies, 2020)
Crossing borders is a perilous undertaking, as this time of migrations and pandemics teaches us. Also for language-related cultural goods such as literary works, crossing those borders requires a lot of planning, strategic insights and a love for language and literature. After all, on their journey abroad, books bring with them other stories and cultural images, which in turn are filtered, if not manipulated, during the processes of selection and reception in the language of their destination. The study of this image (de)formation is therefore crucial in research into literary transfer. The authors of this collection respond to this by tracing the route of Dutch literature to Southern Europe and studying the image of Flanders and the Netherlands as expressed in translations through a combination of imagological and sociological translational findings. The conclusions in this collection show that the study of image formation in literary transfer can break through stereotypes and increase cultural awareness: crossing borders means pushing boundaries.